An Estimate of the Influence of the Compressor Stability Margin on the Thrust of a Turbojet Engine - M. Orkisz (Engineering Transactions)
The relations derived in the paper make it possible to analyze. the influence of the compressor stability margin upon the thrust of a turbo jet engine. The engines operating within the economy range (minimum fuel consumption) and optimum range (maximum thrust) are considered.